New look at performance appraisal for scientists and engineers - Wilson, Donald K. (Research management (Now: research technology management))
Donald K. Wilson, Roland Mueser and Joseph A. Raelin call for complementing the traditional management-centered appraisal with a "professional development" appraisal.